Civitas et Urbs: O projeto neoclássico na cidade da Parahyba (1858-1889) - Assunção, Jessica Soares Rabello (2022)
Among the various conceptualizations around the idea of the city, its content is generally understood as a set of social and also physical qualities, represented here by the terms civitas and urbs respectively. Based on this understanding, this research has as object of study the neoclassical language and its influence on the urban landscape of the city of Parahyba (currently João Pessoa) during the imperial period. The investigation is based on a double meaning of the neoclassical project, which would include, firstly, its civic dimension (culture, civility), related to the civilizing ideals of the Empire of Brazil; and also its material aspects, related to the architectural language itself (shape, volumetry). In this sense, the Campo do Conselheiro Diogo, currently Praça Pedro Américo, is adopted as case study, as it constitutes the most emblematic street of neoclassicism in the capital, since it was delimited by three examples of the style - the Santa Roza theater, the Quartel de Linha and the Provincial Treasury – and for being located exactly in the central region of the city at the time, whose formation and relevance was directly linked to the presence of these buildings. In short, we sought to investigate the existence of a neoclassical project on the urban scale and how it contributed to forging the image of the capital in the 19th century, translating, through architecture, the civilizing and progressive discourse that shaped society at the time. For this, the study unfolded through documentary research, using primary sources such as the reports of the presidents of the province and the press publications, which revealed the influence of the national ideology on the culture of Parahyba during the 19th century. Considering the material dimension, the physical constitution of the city, the study was supported by iconographic and cartographic records, from which it was possible to analyze the general implantation of neoclassical buildings and their importance in the layout of the city, especially in the Campo do Conselheiro Diogo, as well as the physiognomic features of this architectural repertoire and its role in the 19th century urban landscape. Given the emphasis of the study, the recognition of this historical period in Parahyba contributes to the understanding of a national process, which was not restricted to the metropolises of the Empire, but encompassed several provinces of the Northeast that, even not corresponding to the economic and social standards of the Court, assimilated the imperial ideology through the construction of new urban scenarios. It is worth mentioning that the period in question precedes a phase marked by profound changes in the city's landscape, both in terms of its architecture, by the superposition of new modernizing languages, and in the remodeling of public spaces themselves. The irreversibility of these transformations and the lack of knowledge about the aforementioned architectural collection point to the need to recognize their importance for the city of Parahyba, seeing them not only as isolated monuments, but as component signs of the image and urban history of the capital in the 19th century.